PENGARUH HARGA DAN KUALITAS IKAN TERHADAP PENJUALAN IKAN DI TPI MUNCAR MENURUT PERSPEKTIF ISLAM - M. Khanif Ardzani; Afria Rachmawati; Maisatun Jannah (NATUJA: Jurnal Ekonomi Syariah, 2026)
This study aims to analyze the partial and simultaneous influence of price and fish quality on fish sales at TPI Muncar from an Islamic perspective. This research employs a quantitative approach with a causal associative type. The sampling technique used is purposive sampling, with a total of 70 active fish traders at TPI Muncar as respondents. The independent variables in this study are price (X1) and quality (X2), while the dependent variable is fish sales (Y). Data analysis techniques include multiple linear regression analysis tested through t-test, F-test, and the coefficient of determination (R²). The results of the study show that, partially, price has a significant effect on fish sales (t-count 5.426 > t-table 1.668; sig. 0.000 < 0.05) and fish quality also has a significant effect on fish sales (t-count 4.373 > t-table 1.668; sig. 0.000 < 0.05). Simultaneously, price and fish quality have a significant effect on fish sales (F-count 223.015 > F-table 3.13; sig. 0.000 < 0.05). The coefficient of determination (R²) is 0.692, which means that 69.2% of the variation in fish sales is influenced by price and quality, while the remaining 30.8% is influenced by other factors outside this study.